2021
DOI: 10.1007/s00261-021-03216-3
|View full text |Cite
|
Sign up to set email alerts
|

Update on quantitative radiomics of pancreatic tumors

Abstract: Radiomics is a newer approach for analyzing radiological images obtained from conventional imaging modalities such as computed tomography, magnetic resonance imaging, endoscopic ultrasonography, and positron emission tomography. Radiomics involves extracting quantitative data from the images and assessing them to identify diagnostic or prognostic features such as tumor grade, resectability, tumor response to neoadjuvant therapy, and survival. The purpose of this review is to discuss the basic principles of rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 89 publications
(111 reference statements)
0
11
0
Order By: Relevance
“…The inadequate quality of radiomics studies has been addressed repeatedly [15][16][17][18][19][20][21][22][23][24][27][28][29]. In accordance with previous reviews, several items were always lacking including test-retest analysis, phantom study, cutoff analysis, and cost-effectiveness analysis in RQS, the blinded method during outcome assessment, sample size calculation, and handling of missing data in TRIPOD, and details of image preprocessing in selected IBSI items.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The inadequate quality of radiomics studies has been addressed repeatedly [15][16][17][18][19][20][21][22][23][24][27][28][29]. In accordance with previous reviews, several items were always lacking including test-retest analysis, phantom study, cutoff analysis, and cost-effectiveness analysis in RQS, the blinded method during outcome assessment, sample size calculation, and handling of missing data in TRIPOD, and details of image preprocessing in selected IBSI items.…”
Section: Discussionmentioning
confidence: 90%
“…Our results implied that the level of evidence supporting clinical application and the overall study quality were suboptimal in pancreatitis radiomics research, requiring significant improvement. Several reviews have summarized the use of radiomics in multiple pancreatic diseases from pancreatic cystic lesions to pancreatic tumors [15][16][17][18][19][20][21][22]. A comprehensive review reported that most of the pancreatic radiomics studies investigated focal pancreatic lesions, but only four studies discussed the pancreatitis [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of CT and more specifically CT radiomics as a prognostic indicator has been used in other cancers such as non-small cell lung cancer, renal cell carcinoma and colorectal cancer (28,32). In a retrospective study, Khalvati et al (28) assess the prognostic value of CT-derived radiomic features for resectable PDAC and identified several radiomic features which were statistically significant for prognostication of overall survival.…”
Section: Ctmentioning
confidence: 99%
“…In recent years, novel radiomics and radiogenomics studies have provided new ideas for the evaluation of tumors through deep learning and machine learning (ML) algorithms [8][9][10][11][12][13]. Recent studies have found that radiomics models contribute greatly to the individualized evaluation of pancreatic lesions, such as tumor detection, classification, differentiation, and antitumor drug effect prediction [14][15][16][17][18]. In addition, pancreatic cystic lesions have been categorized using radiomics methods in multiple studies [19,20].…”
Section: Introductionmentioning
confidence: 99%